STRATEGI KEBIJAKAN TEKNO EKONOMI PENGELOLAAN GAS IKUTAN (ASSOCIATED GAS) - Zulkifli Rangkuti (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
The amount of gas owned by Indonesia and the declining production of oil fuel (BBM) in Indonesia, has prompted the government to change its policy which has directed the use of fuel into the fuel gas (CNG) as an inexpensive alternative energy and environmentally friendly. Based on the conducted research to determine the strategic direction of the management policy of follow-up of gas in West Monument Square. The study used data analysis methods analitycal hierarchy process (AHP) to develop strategies for policy direction in the management of follow-up of gas in West Monument Square. The results showed that follow-up alternative gas management policy to be developed in the West Monument Oil Field is the use of liquified petroleum gas (LPG). The expected goal in developing the use of LPG is the maintenance of environmental quality in order to clean development mechanism (CDM). To achieve these objectives, the most influential factor was government policy in addition to the available human resources, natural resources (availability of follow-up gas), capital, technology, and infrastructure. Therefore we need government policies and increasing the quality of human resources in the management of follow-up of gas in West Monument lapanagn. Current government policy, especially related to the management there has been no follow-up gas, so that the management was more referring to the policy on the development of energy resources in general. Human resource (HR) is qualified to have the skills to manage human resources management of the industry but have the knowledge and awareness of the importance of protecting the environment. Keywords: Policies, follow-up gas management, AHP, ISM